THE STUDY OF STUDENTS’ ERRORS IN TRANSFERRING L1 TO L2 AT FIRST YEAR STUDENTS OF PRIVATE UNIVERSITY IN SINTANG - Sijono Sijono; Ilinawati Ilinawati (Journal of English Educational Study (JEES), 2018)
This study was about the students’ errors in transferring L1 to L2.It  was qualitative research and involved the first years students of Pendidikan Bahasa Inggris of private University in Sintang. The research purpose was to investigate the sources of errors that most caused the students made errors in transferring L1 to L2. There are mainly two major sources of errors in second language learning; they are Interlingual errors and intralingual errors, but this study focused on intralingual factors. To collect the data the researchers used a test in the form of translating L1 to L2. The test consisted of some grammatical aspects such as tenses, propositions and vocabularies. Based on the data analysis the researchers found 80 cases of errors made by the students. In which one student could make more than one cases of errors in their test. The research finding showed that there were six major sources of intralingual factors appeared in the analysis, they were simplification, overgeneralization, fosilization, avoidance, inadequate learning and false concepts hyphothesized. The biggest factor that caused the students made errors was inadequate learning. Transfer errors happened due to the lack of information about the target language.Keyword: Students’ Error, Transferring L1 to L2